Differential Regulation of Gene Expression in Lung Cancer Cells by Diacyglycerol-Lactones and a Phorbol Ester Via Selective Activation of Protein Kinase C Isozymes - Cooke, Mariana (2019)
Despite our extensive knowledge on the biology of protein kinase C (PKC) and its involvement in disease, limited success has been attained in the generation of PKC isozyme-specifc modulators acting via the C1 domain, the binding site for the lipid second messenger diacylglycerol (DAG) and the phorbol ester tumor promoters. Synthetic eforts had recently led to the identifcation of AJH-836, a DAG-lactone with preferential afnity for novel isozymes (nPKCs) relative to classical PKCs (cPKCs). Here, we compared the ability of AJH-836 and a prototypical phorbol ester (phorbol 12-myristate 13-acetate, PMA) to induce changes in gene expression in a lung cancer model. Gene profling analysis using RNA-Seq revealed that PMA caused major changes in gene expression, whereas AJH-836 only induced a small subset of genes, thus providing a strong indication for a major involvement of cPKCs in their control of gene expression. MMP1, MMP9, and MMP10 were among the genes most prominently induced by PMA, an efect impaired by RNAi silencing of PKCα, but not PKCδ or PKCε. Comprehensive gene signature analysis and bioinformatics eforts, including functional enrichment and transcription factor binding site analyses of dysregulated genes, identifed major diferences in pathway activation and transcriptional networks between PMA and DAG-lactones. In addition to providing solid evidence for the diferential involvement of individual PKC isozymes in the control of gene expression, our studies emphasize the importance of generating targeted C1 domain ligands capable of diferentially regulating PKC isozyme-specifc function in cellular models.